Malnutrition and low muscle strength are independent predictors of clinical outcomes and healthcare costs after liver transplant. (April 2022) - Chapman, Brooke; Goh, Su Kah; Parker, Frank; Romero, Sarah; Sinclair, Marie; Gow, Paul; Ma, Ronald; Angus, Peter; Jones, Robert; Luke, Jacqueline; Muralidharan, Vijayaragavan; Testro, Adam
Summary: Background & aims: Malnutrition and sarcopenia are associated with increased morbidity and mortality in cirrhosis but conflicting data are reported after liver transplantation (LT), with little known about the economic burden of malnutrition at LT. This study aims to investigate the impact of pre-transplant malnutrition and muscle strength on post-transplant clinical outcomes and healthcare costs. Methods: Pre-transplant nutritional status (via subjective global assessment, SGA) and handgrip strength (HGS) were assessed in patients transplanted from 2009-2017. Descriptive statistics and regression analysis were used to analyse the association between nutrition and muscle function with post-LT clinical outcomes and hospital costs. Results: 373 patients (70% male, median age 55 [IQR: 47, 60]) were transplanted, with 79% malnourished and mean HGS 31.4 ± 9.35 kg for males and 17.6 ± 5.78 kg for females. Malnutrition and reduced HGS independently predicted adverse post-transplant outcomes. ICU length of stay (LOS) was associated with severe malnutrition (HR (time to discharge (TTD)) 0.706, p = 0.014) and low HGS (HR (TTD) 0.692, p = 0.003); hospital LOS with severe malnutrition (HR (TTD) 0.759, p = 0.049) and low HGS (HR (TTD) 0.730, p = 0.011), and post-transplant infection with severe malnutrition (OR 1.76, p = 0.042) and low HGS (OR 1.83, p = 0.015). Accordingly, hospital costs were 30% higher in severely malnourished compared to well-nourished recipients (p = 0.012). Neither malnutrition or impaired HGS were associated with post-transplant mortality. Conclusions: This large cohort study demonstrates malnutrition and muscle weakness are independently associated with early post-transplant morbidity, namely infection and ICU and hospital LOS; with significantly increased hospital costs. Strategies to combat malnutrition and deconditioning pre-transplant may improve patient and health system outcomes after LT.